Factors contributing to rapidly increasing rates of cesarean section in Armenia: a partially mixed concurrent quantitative-qualitative equal status study - Meri Tadevosyan; Anna Ghazaryan; Arusyak Harutyunyan; Varduhi Petrosyan; Adam Atherly; Kim Hekimian (BMC, 2019)
Abstract Background Armenia has an upward trend in cesarean sections (CS); the CS rate increased from 7.2% in 2000 to 31.0% in 2017. The purpose of this study was to investigate potential factors contributing to the rapidly increasing rates of CS in Armenia and identify the actual costs of CS and vaginal birth (VB), which are different from the reimbursement rates by the Obstetric Care State Certificate Program of the Ministry of Health. Methods This was a partially mixed concurrent quantitative-qualitative equal status study. The research team collected qualitative data via in-depth interviews (IDI) with obstetrician-gynecologists (OBGYN) and policymakers and focus group discussions (FGD) with women. The quantitative phase of the study utilized the bottom-up cost accounting (considering only direct variable costs) from the perspective of providers, and it included self-administered provider surveys and retrospective review of mother and child hospital records. The survey questionnaire was developed based on IDIs with providers of different medical services. Results The mean estimated direct variable cost per case was 35,219 AMD (94.72 USD) for VB and 80,385 AMD (216.19 USD) for CS. The ratio of mean direct variable costs for CS vs. VB was 2.28, which is higher than the government's reimbursement ratio of 1.64. The amount of bonus payments to OBGYNs was 11 fold higher for CS than for VB indicating that OBGYNs may have significant financial motivation to perform CS without a medical necessity. The qualitative study analysis revealed that financial incentives, maternal request and lack of regulations could be contributing to increasing the CS rates. While OBGYNs did not report that higher reimbursement for CS could lead to increasing CS rates, the policymakers suggested a relationship between the high CS rate and the reimbursement mechanism. The quantitative phase of the study confirmed the policymakers' concern. Conclusion The study suggested an important relationship between the increasing CS rates and the current health care reimbursement system.